PEMBUATAN PROGRAM APLIKASI PEMESANAN BARANG BERBASIS ANDROID DI PT. TEKNINDO MEGA SEJATI - Edric Aryanto; Ery Dewayani; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Technological developments have developed very rapidly so as to create and influence progress in various fields. One area that has followed this development is the ordering business on line. To keep abreast of this technological development, business people create appropriate sales ideas with currently developing technology. Utilization of this technology can be used in various fields, one of which is the online sales business. Pt. Teknindo Mega Sejati is a company that engaged in the sale of material goods. Constraints faced when ordering goods are recording manually so that customers have to ask whether stock is available or not and the recording of orders is only in the form of physical data so it is vulnerable to loss. There are these obstacles an Android-based material goods ordering application program was made at Pt. Teknindo Mega Sejati. This program application is designed using the Prototype method. Database used to store data using XAMPP MySQL. To display the application menu, the framework used is flutter with darts programming language. The result is to create selling app based on android and making it for consumers and Pt. Teknindo Mega Sejati to obtain information and place orders.